Is the Rupee over-valued? - Jaimini Bhagwati; Abheek Barua; M. Shuheb Khan (Indian Council for Research on International Economic Relations (ICRIER), 2015)
The paper's objective is to examine whether the Indian Rupee was fairly valued as of end March 2015. First, the movements of the trade weighted real effective exchange rate (REER) of the Rupee are tracked over the last ten years. Next, the underpinnings of the Harrod-Balassa-Samuelson effect, which suggests taking changes in productivity levels into account in arriving at reliable estimates of exchange rates, and associated studies, are assessed. The paper also discusses varying approaches to Behavioural Equilibrium Exchange Rate (BEER) models and uses one to analyse whether the Rupee is fairly valued. The conclusion of the paper that the Rupee is substantially over-valued is based on a comparison of results obtained using differing methodologies.
Keywords: E00; E30; F31; F32; F41; C50; 330; Real effective exchange rate; capital inflows; inflation; export growth; Harrod-Balassa-Samuelson; Behavioural Equilibrium Exchange Rate